2015 Atomic Spectrometry Update – a review of advances in X-ray fluorescence spectrometry and their applications. Issue 9 (19th September 2015) - West, Margaret; Ellis, Andrew T.; Potts, Philip J.; Streli, Christina; Vanhoof, Christine; Wobrauschek, Peter
<x xml:space="preserve">Abstract</x> This review covers developments in and applications of XRF techniques such as EDXRF, WDXRF, TXRF, XRF microscopy using technologies such as synchrotron sources, X-ray optics, X-ray tubes and detectors in laboratory, mobile and hand-held systems.